LWDG Method for a Multi-Class Traffic Flow Model on an Inhomogeneous Highway (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we apply the discontinuous Galerkin method withLax-Wendroff type time discretizations (LWDG) using the weightedessentially non-oscillatory (WENO) limiter to solve a multi-classtraffic flow model for an inhomogeneous highway, which is a kind ofhyperbolic conservation law with spatially varying fluxes. Thenumerical scheme is based on a modified equivalent system which iswritten as a "standard" hyperbolic conservation form. Numericalexperiments for both the Riemann problem and the traffic signalcontrol problem are presented to show the effectiveness of thesemethods.